Manajemen Marketing Asuransi Syariah Untuk Meningkatkan Minat Masyarakat Pada PT Prudential Komplek Merbau Mas - Irdayanti, Nadila; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This research was conducted to advance the marketing level of Islamic insurance and attract public interest, especially in the city of Medan at Pt Prudential, the contents of this journal were input based on data from PT Prudential Medan branch. This research was conducted based on a qualitative descriptive method, a research method by collecting real/true data, then compiled into an invention or what is commonly called a journal so that it can provide actual facts about how to design marketing marketing to PT Prudential branch customers. Medan. Marketing can be interpreted as one of the sciences that has developed for quite a long time in the community, especially the city of Medan. Therefore, the company/office must be able to make marketing something that has a positive impact on the progress or success of a company in marketing its products. Insurance in Indonesia has ample opportunity to grow in line with the growth of the Islamic financial market. Outreach to the public is one way to increase product sales in the insurance world. In terms of vision and mission, we already know what agents must do to attract public interest in joining as insurance customers, therefore a good communication image must be built to facilitate this.